The City as Illusion and Promise - Barbaza, Remmon E (Archīum Ateneo, 2019)
In The City as Illusion and Promise, the author examines the claim (by Henri Lefebvre, and later David Harvey) that the city no longer exists, at least as we know it. What we have instead is merely an illusion, something that Martin Heidegger also implies in some of his later writings, notably his seminal work on the essence of technology. In confronting such an extreme proposition, the author first raises a conceptual problem: Is the city a city insofar as it is not a province? And vice versa? But the conceptual problematic of course is also manifested in actual material conditions. Can the city exist without the province? What is the relationship between the city and province? While the author finds merit in recognizing the illusion that is the city, he nonetheless invites the reader to imagine other possibilities, however impossible they may seem: Either we settle with the illusion that is the city of our age, or reimagine and work towards the realization of new possibilities for the city, one that restores and respects the balance in nature that we have for so long forgotten and covered over with our illusions.